Telecommuting in the hybrid model: alternative for organizations (Revista de Investigaciones Universidad del Quindío, 2022)
The pandemic of COVID-19 has generated changes in the form of work in organizations, the Use of technologies of information and communication have been developed models like telework that contribute various benefits to the companies. This review article describes the advantages of telework in the hybrid model in organizations. The benefits of the hybrid model were obtained as the perfect formula to balance the results and minimize the disadvantages of pure telework. It is concluded that organizations must generate the metrics of the workers in order to be able to measure their productivity no matter in which physical space they are.
Keywords: Work; ICT; Organization